DEKONSTRUKSI DAN REPRESENTASI KEBUDAYAAN UNTUK MEMAHAMI MODEL KOMUNIKASI KAUM MARGINAL - Koeswinamo, Koeswinamo (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
There are two main ideas in this article, how deconstruction and reconstruction models can be used in human communication process, especially in understanding marginalized communities that all this time are powerless in sounding their existance. The emerging of deconstruction has become an attached character of post-structuralism that criticize the determinations of structuralism. Structuralism approach always accentuate the binary opposition, a pair of related terms or concepts that are opposite in meaning, so it create levels of hierarchy, resulting inferior culture and the correctness is only for the dominant and powerful ones. Through the language perspective, deconstruction try to point out the limitations of construction in the form of writing, and try to involve the power of spoken language as a cultural convention that deserved to get the attention. On the other side, representation accuracy can be a model to object who presumed wrong doing. In other words, representation can be a prevention mechanism to human behavior that violate the community signs; so that the wrong doings can not be happenned again. Nevertheless, disciplinary or punishment form resulting from representation is not to omit the violation, but to avoid the recurrence of an event.